Analisis Korelasi Rank Spearman pada Hubungan antara Kemiskinan dan Kejadian Underweight pada Balita di Jawa Barat - Dea Yustia Diningrum; Suliadi (Bandung Conference Series: Statistics, 2024)
Abstract. Nutritional problems in toddlers are important indicators of public health, specifically in developing countries like Indonesia. Nutritional challenges in Indonesia include issues related to undernutrition (underweight, stunting, and wasting), overnutrition (obesity or overweight), and micronutrient deficiencies. Although stunting often receives the most attention in national health programs, the issue of underweight still requires special focus, as it can be the procursor to more serious nutritional problems. Poverty is one of the main factors influencing the nutritional status of children under five. Economic disadvantages limit families’ access to nutritious food, healthcare, education, and adequate sanitation. This study used Spearman rank correlation analysis to examine the relationship between poverty and the incidence of underweight among toddlers in West Java Province in 2023. It is obtained that there is a significant relationship between poverty and the incidence of underweight among toddlers in West Java Province, which falls into the category of a strong relationship, with a positive direction between the two variables. Thus, the higher the level of poverty, the higher the incidence of underweight among toddlers in West Java. Abstrak. Masalah gizi pada balita merupakan salah satu indikator penting dalam menilai kesehatan masyarakat, terutama di negara berkembang seperti Indonesia. Tantangan gizi di Indonesia meliputi masalah undernutrition (berat badan kurang, stunting dan kurus), overnutrition (obesitas atau kegemukan), serta kekurangan gizi mikro. Meskipun stunting sering menjadi fokus utama dalam program kesehatan nasional, masalah underweight (berat badan kurang) tetap memerlukan perhatian khusus karena kondisi ini dapat menjadi awal dari masalah gizi yang lebih serius. Kemiskinan adalah salah satu faktor utama yang mempengaruhi status gizi balita. Ketidakmampuan ekonomi membatasi akses keluarga terhadap makanan bergizi, pelayanan kesehatan, pendidikan, dan sanitasi yang layak. Peneliti menggunakan analisis korelasi rank Spearman untuk mengkaji hubungan antara kemiskinan dan kejadian underweight pada balita di Provinsi Jawa Barat pada tahun 2023. Hasil dari penelitian ini adalah terdapat hubungan yang signifikan antara kemiskinan dan kejadian underweight pada balita di Provinsi Jawa Barat yang termasuk dalam kategori hubungan yang kuat dan terdapat arah hubungan yang positif di antara kedua variabel. Dengan demikian, semakin tinggi tingkat kemiskinan, semakin tinggi pula kejadian underweight pada balita di Jawa Barat.